Rediscovery of Omalodes (Omalodes) fassli Bickhardt, 1911 (Coleoptera: Histeridae) in Colombia and first report of the species on banana crops (Musa paradisiaca) - Torres Domínguez, Diana Marcela; Trevisan Leivas, Fernando Willyan; Londoño Sanchez, Carolina; Montoya Lerma, James; Armbrecht, Inge (Instituto de Ecología, A.C., 2018)
After 106 years, the presence of Omalodes (Omalodes) fassli in Colombia has been confirmed, and new distributional data for the country has been provided. This is the first report of the species on banana crops (Musa paradisiaca), it highlights its potential role in the control of the banana weevil, a key pest of this crop worldwide.